Politik Islam : Dari Perilaku hingga Pemikiran Politik - Alkhendra Alkhendra (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2013)
One of measures taken by the Prophet Muhammad as a reflection of political behavior is often the Prophet engaged in various agreements, one of which is monumental is the agreement of Medina (Medina Charter), are involved in the battle which is another form of political phenomena. After Muhammad's death, the phenomenon of political life increasingly seen more clearly, which is marked by events when the Prophet Died. The phenomenon of Islamic political life can also be seen from the succession process that occurs in three caliphs.